Financial statement. 8 July 1938 - Basque Children's Committee
1938-07 038-0129-002 PRIVATE AND CONFIDENTIAL FINANCIAL STATEMENT. July 8th, 1938. BANK BALANCE AS AT JULY 6th, 1938: Basque Children's Committee: £ 400. 0. 0. National Joint Committee for Spanish Relief. (General Reserve) £1250. 0. 0. £1650. 0. 0. Results of Special Stavert Appeal, to July 12th, 1938. £ 950.(Nett ) ESTIMATED EXPENDITURE TO END OF JULY, 1938: Salaries (Staff) £ 92. 10. 0. Maintenance of Homes (approx.) 1,000 0. 0 . Rent and Telephone 62. 10. 0. Petty Cash 20. 0. 0. Insurance (Employers' Liability and Fire) (approx.) 50. 0. 0. £1,225. 0. 0. OUTSTANDING ACCOUNTS: War Office £ 600. 0. 0. Eastcliff House, Dilapidations (balance ) 143. 0. 0, Swansea (Home closing) 288. 9. 0. Witney (half cost of expenses April 23rd to June 4th) 60. 8. 11. Rownhams Mount (outstanding bills) 70. 0. 0. Miss Britton, Compensation. (balance) ? 69. 0. 0, £1,230. 14. 11. 292/946/38/129(II)